Design and evaluation of the empennage for reconnaissance UAV - Izzan Hairi, Mohd Ibrahim (2009)
This project describes and explains the process to estimate conceptual design and sizing of a new small unmanned aerial vehicle (UAV). The small UAV was designed for use in the civil reconnaissance missions such as aerial photography and agriculture monitoring and can be expand for use in the government sectors. The length of the UAV is 1.2 meter and the wing span is 2meter. Initially, the mini-UAV designed for loiter at an altitude 1000ft (300meter) and the take-off weight of 3.8kg.This report contains a statistical analysis to determine the weight of the UAV. The study of the similar type of UAV will give the guidelines description during the initial weight analysis. Next, the design covers the aircraft sizing analysis which is follow the Federal Aviation Regulations (FAR) sizing requirements as the basis of airworthiness purpose. The sensitivity analysis will help the designer to find the parameters that dependent to takeoff weight of the UAV. This UAV will implement the conventional tail configuration based on empennage sizing. This report also contains the analysis of the airfoil and finally the design of the empennage and the UAV will be done by CAD software.